2002
DOI: 10.1016/s0006-3495(02)75572-0
|View full text |Cite
|
Sign up to set email alerts
|

A New Deformation Model of Hard α-Keratin Fibers at the Nanometer Scale: Implications for Hard α-Keratin Intermediate Filament Mechanical Properties

Abstract: The mechanical behavior of human hair fibers is determined by the interactions between keratin proteins structured into microfibrils (hard alpha-keratin intermediate filaments), a protein sulfur-rich matrix (intermediate filaments associated proteins), and water molecules. The structure of the microfibril-matrix assembly has already been fully characterized using electron microscopy and small-angle x-ray scattering on unstressed fibers. However, these results give only a static image of this assembly. To obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 32 publications
2
61
0
1
Order By: Relevance
“…This low influence of the IF/KAP disulfide network on the follicle mechanics, despite its extremely high density, is likely a consequence of the immersion in PBS during our experiments. Due to the hygroscopic nature of the KAP matrix, it will swell in water, whereas the IFs show only little water uptake (45), causing a weakening of ionic and H-bond interactions. This swelling could minimize the mechanical contribution of the matrix in our measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This low influence of the IF/KAP disulfide network on the follicle mechanics, despite its extremely high density, is likely a consequence of the immersion in PBS during our experiments. Due to the hygroscopic nature of the KAP matrix, it will swell in water, whereas the IFs show only little water uptake (45), causing a weakening of ionic and H-bond interactions. This swelling could minimize the mechanical contribution of the matrix in our measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of IFs, the shear modulus cannot be neglected because the filament is built by the longitudinal and lateral interaction of ∼45 nm long rods that have the potential to slide longitudinally past each other. 15,17,28 Hence, a cross-linker such as glutaraldehyde is able to create covalent bonds between adjacent dimer rods that should reduce the amount of sliding. As expected from equation (5), glutaraldehyde-fixed IFs exhibit a significantly higher bending stiffness of ∼900 MPa that, to first (4)).…”
Section: Discussionmentioning
confidence: 99%
“…2 Knowledge about the IF's mechanical properties and their functional role in cells has increased in the last few years thanks to a series of studies mainly performed at the filament network [11][12][13][14] and bundle levels. 15,16 The only studies at the single filament level were done by Mücke, Kreplak, and coworkers. 17,18 Mücke and colleagues used imaging by atomic force microscopy (AFM) to measure the apparent persistence length, λ, of vimentin IFs.…”
Section: Introductionmentioning
confidence: 99%
“…X-Ray diffraction studies have revealed that the effect of water must involve a combination of a sliding and molecular stretching process. 7 Indeed, at low humidity, it is well known that the˛-helix !ˇ-sheet transition occurs as a consequence of macroscopic stress. 8 -10 Analogy with less complex, organized materials, such as polymer fibres, shall be considered in this study.…”
Section: Introductionmentioning
confidence: 99%